Analyzing Bank Aceh’s Reputation: The Mediating Role of CSR in Governance and Service Quality - Fitrah, Ramdansyah (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Reputation is a crucial intangible asset for banks, as it builds customer trust, attracts investors, and strengthens competitiveness in a competitive market. This study examines how corporate governance and service quality influence the reputation of Bank Aceh, with Corporate Social Responsibility (CSR) acting as a mediating factor. Using a quantitative method and purposive sampling, data were collected from 100 customer respondents and external stakeholders who have been engaged with Bank Aceh for at least one year and are familiar with its services and CSR activities. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The findings show that both corporate governance and service quality positively and significantly affect the bank's reputation. Additionally, corporate governance significantly impacts CSR, whereas service quality does not. CSR itself has a positive and significant effect on the bank’s reputation. Furthermore, CSR mediates the relationship between corporate governance and reputation but does not mediate the link between service quality and reputation. These results underline CSR’s strategic function in connecting internal governance with stakeholder perceptions, particularly within the setting of a regional Islamic bank.